2019
DOI: 10.1016/j.envpol.2019.113054
|View full text |Cite
|
Sign up to set email alerts
|

Different cardiorespiratory effects of indoor air pollution intervention with ionization air purifier: Findings from a randomized, double-blind crossover study among school children in Beijing

Abstract: Indoor air pollution is associated with numerous adverse health outcomes. Air purifiers are widely used to reduce indoor air pollutants. Ionization air purifiers are becoming increasingly popular for their low power consumption and noise, yet its health effects remain unclear. This randomized, double-blind crossover study is conducted to explore the cardiorespiratory effects of ionization air purification among 44 children in Beijing. Real or sham purification was performed in classrooms for 5 weekdays. Size-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Notably, the level of exposures may play crucial roles in the health effects of NI. Beneficial effects of NIs have been observed when the NI levels were comparable to those from the forest environment, 15 while adverse effects were documented for extremely high NI levels when generated by NIAPs 14,18 . In the present study, NI exposure duration was longer and NI levels were substantially higher as compared to a natural forest or oceanic exposure scenario and even to those used in previous studies of pure NI generated under laboratory conditions.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Notably, the level of exposures may play crucial roles in the health effects of NI. Beneficial effects of NIs have been observed when the NI levels were comparable to those from the forest environment, 15 while adverse effects were documented for extremely high NI levels when generated by NIAPs 14,18 . In the present study, NI exposure duration was longer and NI levels were substantially higher as compared to a natural forest or oceanic exposure scenario and even to those used in previous studies of pure NI generated under laboratory conditions.…”
Section: Discussionmentioning
confidence: 39%
“…The modern negative ion air purifier (NIAP) technology, on the contrary, does not generate ozone but produce substantial amount of negative air ions. Negative ions have been credited with “mysterious” health benefits such as promoting physiological health and boosting immune systems 13,14 . A limited number of studies indeed have shown some health benefits of short‐term exposures to “pure” negative ions, when the technology was not used to remove airborne particles, in humans and animals 15‐17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also no effects of IG use on measures of lung function, vascular tone, arterial stiffness, or inflammation. In a similar study of 44 children in Beijing classrooms, Dong et al [68] reported that 5 days of IG use decreased PM 2.5 and BC, improved lung function and reduced airway inflammation, but did not alter blood pressure. However, the study also found that negative ions were associated with detrimental effects on HRV.…”
Section: Air Purifiersmentioning
confidence: 95%
“…Besides, negative oxygen ions can improve people's sleep quality and blood circulation, enhance cardiopulmonary functions, aerobic metabolism, and recovery after movements, as well as cure pneumoconiosis by integrating with low load aerobic Yoga [11][12][13][14][15]. An NAI generator can eliminate particulate matters in the atmosphere while filtering and inactivating aerosolized viruses [16][17][18][19]. Therefore, an investigation of the NAI concentration is of great significance for human physical and mental health and the improvement of air quality.…”
Section: Introductionmentioning
confidence: 99%